The Relationship Between Intrahospital Mortality and P-Wave Dispersion in COVID-19 Patients - Kucuk, Ugur; Bolayir, Hasan Ata (Galenos Publ House, 2021)
Aim: P-wave dispersion (PWD) is a noninvasive electrocardiographic (ECG) marker of atrial remodeling. Inflammations are likely to cause atrial remodeling. This study aims to determine the relationship between PWD and intrahospital mortality in Coronavirus disease-2019 (COVID-19) patients. Methods: One hundred eighty-nine patients who tested positive for polymerase chain reaction for a diagnosis of COVID-19 between March 2020 and January 2021 were included in the cross-sectional study. PWD was calculated from the pre-treatment ECG of all patients at the time of hospitalization. Results: Mean PWD values were numerically and statistically significant in the group who died in hospital compared to the group discharged after recovery (46.37 +/- 19.00 ms vs. 31.86 +/- 11.08 ms, p<0.001). Regardless of gender, regression analysis found an independent relationship between PWD values and mortality in COVID-19 patients. In the receiver operating characteristic curve analysis, PWD values above 34 ms had 73% sensitivity and 69% specificity in predicting all-cause mortality in COVID-19 patients (area under the curve: 0.737, confidence interval: 0.666-0.808, p<0.001). Conclusions: PWD was associated with in-hospital mortality in COVID-19 patients. The findings of this study demonstrate that the PWD values calculated at the time of hospitalization can be helpful in determining the prognosis of COVID-19 patients.
Keywords: P-wave dispersion; SARS-CoV-2; COVID-19; electrocardiography; mortality